Impact of E-service quality on E-customer loyalty: The Role of E-customer satisfaction as Mediator - Sefnedi, Sefnedi; Alfarizi, Ahmad (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – This paper seeks to examine the mediator effect of e-customer satisfaction on the relationship between e-service quality and e-customer loyalty. Methodology/approach – The population in this study was all OVO e-money customers in Padang city. The sampling technique used a non-probability approach, namely the purposive sampling. In the data analysis, 151 samples were used as a sample size. In order to test hypotheses, the software of SEM-PLS was performed. Findings – It was found that e-service quality has positive effect on e-customer satisfaction and e-customer loyalty. The variable of e-customer satisfaction is also found to have positive effect on e-customer loyalty. Furthermore, the e-customer satisfaction is proven to mediate the relationship between e-service quality and e-customer loyalty. Novelty/value – e-customer loyalty has been an important factor in the e-marketing. However, the determinants of e-customer loyalty are still far from conclusive.